CrossMDA-SPL: uma abordagem para gerência de variabilidades dirigida por modelos e aspectos - Filgueira, Geam Carlos de Araújo (2009)
This paper proposes a systematic approach to management of variability modelsdriven and aspects using the mechanisms of approaches Aspect-Oriented Software Development (AOSD) and Model-Driven Development (MDD). The main goal of the approach, named CrossMDA-SPL, is to improve the management(gerência), modularization and isolation ou separation of the variability of the LPSs of architecture in a high level of abstraction (model) at the design and implementing phases of development Software Product Lines (SPLs), exploiting the synergy between AOSD and MDD. The CrossMDA-SPL approach defines some artifacts basis for advance the separation clear in between the mandatory (bounden) and optional features in the architecture of SPL. The artifacts are represented by two models named: (i) core model (base domain) - responsible for specify the common features the all members of the SPL, and (ii) variability model - responsible for represent the variables features of SPL. In addition, the CrossMDA-SPL approach is composed of: (i) guidelines for modeling and representation of variability, (ii) CrossMDA-SPL services and process, and (iii) models of the architecture of SPL or product instance of SPL. The guidelines use the advantages of AOSD and MDD to promote a better modularization of the variable features of the architecture of SPL during the creation of core and variability models of the approach. The services and sub-processes are responsible for combination automatically, through of process of transformation between the core and variability models, and the generation of new models that represent the implementation of the architecture of SPL or a instance model of SPL. Mechanisms for effective modularization of variability for architectures of SPL at model level. The concepts are described and measured with the execution of a case study of an SPL for management systems of transport electronic tickets